Estudo etnobotânico sobre plantas medicinais com agentes comunitários de saúde e especialistas locais na zona da mata paraibana, nordeste do Brasil - Maia, Anne Carolinne de Paiva (2019)
The use of medicinal plants is historically ancient and accompanies the entire history of humanity. Ethnobotany is a field of knowledge dedicated to the study of relationships between human societies and plants, and the use of medicinal plants is one of its main research themes. Thus, this study aimed to compare the knowledge of medicinal plants between community health agents (ACS) and local specialists in the community of Timbó, municipality of Jacaraú, Paraíba, Northeast Brazil. Semi-structured interviews were conducted addressing the local name of plants, their indications, parts used and preparation method. Data on the local importance of the species were analyzed by the Use Value (VU) and Relative Importance (IR) methods. The data obtained in this study indicate great local importance of Dysphania ambrosioides, Mentha arvensis, Lippia alba, Sambucus australis, and Pimpinella anisum. Decoction and infusion were the most relevant preparation methods and leaf, flower and seed were the most used parts. The diseases treated by plants are mainly related to the respiratory and digestive systems. The data show a correspondence between ACS’s and local specialists’ knowledge.